HUBUNGAN ANTARA SELF CONCEPT DAN SOCIAL ADJUSTMENT PADA MAHASISWA DI UNIVERSITAS X - Ninawati , Ninawati; Gracia Alvionita , Agnes; Junique Guineath , Suweny; Rahma Amelia , Putri; Angel , Davilia (Fakultas Psikologi Universitas Tarumanagara, 2024)
As students attain early adulthood, they begin to develop their self-concept. A person's overall perception of themselves, or self-concept, is shaped by their interactions with other people in daily life, which can change over time (Showers et al., 2015). Students who are in strong psychological health may be able to identify their strengths and weaknesses which can help with social adjustment issues. The ability to integrate into a social setting and meet social demands in a constructive and fulfilling way is known as social adjustment. Students who have made social adjustments may find it easier to relate to others and enjoy some social liberties. The purpose of the study was to investigate the relationship between university students' social adjustment and their self-concept. The Tennessee Self- Concept Scale (TSCS) is the instrument used to measure self-concept, and the Social Adjustment Scale, developed by Nadia Safitri (2010) and based on Schneiders' theory, is the instrument used to measure social adjustment. The study's findings demonstrate a strong positive correlation (r (101) = 0.554 and p = 0.000 (p < 0.05) between University X students' self-concept and social adjustment. Accordingly, it may be said that there is a unidirectional relationship between social adjustment and self-concept, the higher a student's level of social adjustment, the higher their self- concept. Good self-concept and social adjustment promote students' well-being and academic potential in the university environment.